Severe Sporotrichosis Caused by Sporothrix brasiliensis: Antifungal Susceptibility and Clinical Outcomes - Vivian Fichman; Fernando Almeida-Silva; Dayvison Francis Saraiva Freitas; Rosely Maria Zancopé-Oliveira; Maria Clara Gutierrez-Galhardo; Rodrigo Almeida-Paes (Journal of Fungi, 2022)
Itraconazole is the first choice for treating sporotrichosis. Amphotericin B is indicated for severe and disseminated forms. The aim of the study was to evaluate the antifungal susceptibility of Sporothrix brasiliensis strains isolated from patients with severe sporotrichosis treated with amphotericin B and correlate with clinical outcomes. Clinical and epidemiological data were obtained from severe sporotrichosis cases caused by S. brasiliensis. Antifungal susceptibility tests against amphotericin B, itraconazole, terbinafine, posaconazole, and 5-flucytosine were performed. Moreover, possible synergisms between amphotericin B and posaconazole or 5-flucytosine were assessed. Relationships between clinical and laboratorial data were then analyzed. Forty-six S. brasiliensis isolates from 37 patients were studied. Clinical forms included disseminated (94.6%) and disseminated cutaneous sporotrichosis (5.4%). The median treatment time was 784 days (range: 7 to 3115 days). Cure occurred in 45.9% of the cases and death due to sporotrichosis in 24.3%. Forty-three (93.5%) S. brasiliensis isolates were classified as wild-type for all the antifungals tested according to their in vitro antifungal susceptibility. There was no synergism for the combinations studied. Finally, we found no association between higher Minimal Inhibitory Concentration (MIC) values of amphotericin B or itraconazole with unfavorable outcomes; however, there were higher MIC values of itraconazole in strains isolated from alcoholic patients. Possibly, clinical factors, such as the extent of dissemination, immunosuppression, and late treatment onset, are the main determinants of patient outcomes, rather than antifungal resistance. The current study suggests that the need to use amphotericin B therapy is not associated with the emergence of S. brasiliensis resistant strains.